Earnings Per Share, Return on Equity, and Debt to Asset Ratio Related to Stock Prices - Pratama, Anggara Bangun; Kurnianingsih, Widiyanti; Santoso, Fahrul Imam (GOVERNORS, 2025)
This study aims to empirically analyze the influence of Earnings Per Share (EPS), Return on Equity (ROE), and Debt to Asset Ratio (DAR) on the stock prices of companies in the financial sector listed on the Indonesia Stock Exchange (IDX). The research uses a quantitative approach with an explanatory design, applying multiple linear regression analysis to simulated panel data for the period 2021–2025. Data were obtained from secondary sources by simulating financial reports and stock prices that realistically reflect historical trends for 10 selected financial companies, resulting in 50 observations. The study employs standard data analysis techniques, including classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation) to ensure that the model fulfills the BLUE (Best Linear Unbiased Estimator) criteria. The results indicate that EPS and ROE have a significant positive effect on stock prices, whereas DAR has a significant negative effect. The high coefficient of determination (R²) confirms that the model explains most of the variability in stock prices. These findings reaffirm that company profitability and equity management efficiency drive stock price appreciation, while an excessive capital structure relying on high debt can lower investor confidence. This study contributes to the existing literature by providing systematic empirical evidence and serves as a practical reference for investors and financial managers in making informed strategic decisions.